Exercise-Induced Changes in Pulmonary Artery Stiffness in Pulmonary Hypertension - Forouzan, Omid; Dinges, Eric; Runo, James R.; Keevil, Jonathan G.; Eickhoff, Jens C.; Francois, Christopher; Chesler, Naomi C. (Frontiers in Physiology, 2019)
Background– Pulmonary hypertension causes pulmonary artery (PA) stiffening, which overloads the right ventricle (RV). Since symptoms of pulmonary hypertension (PH) are exacerbated by exercise, exercise-induced PA stiffening is relevant to cardiopulmonary status. Here we sought to demonstrate the feasibility of using magnetic resonance imaging (MRI) for non-invasive assessment of exercise-induced changes in PA stiffness in patients with PH. Methods–MRI was performed on 7 PH patients and 8 age-matched control subjects at rest and during exercise stress. Main pulmonary artery (MPA) relative area change (RAC) and pulse wave velocity (PWV) were measured from 2D-PC images. Invasive right heart catheterization (RHC) was performed on 5 of the PH patients in conjunction with exercise stress to measure MPA pressures and stiffness index (β). Results– Heart rate and cardiac index were significantly increased with exercise in both groups. In controls, RAC decreased from 0.27±0.05 at rest to 0.22±0.06 with exercise (P<0.05); a modest increase in PWV was not significant (P=0.06). In PH patients, RAC decreased from 0.15±0.02 to 0.11±0.01 (P<0.05) and PWV and β increased from 3.9±0.54 m/s and 1.86±0.12 at rest to 5.75±0.70 m/s and 3.25±0.26 with exercise (P<0.05 for both), respectively. These results confirm increased MPA stiffness with exercise stress in both groups and the non-invasive metrics of MPA stiffness correlated well with β. Finally, as assessed by PWV but not RAC, PA stiffness of PH patients increased more than that of controls for comparable levels of moderate exercise. Conclusion- These results demonstrate the feasibility of using MRI for non-invasive assessment of exercise-induced changes in MPA stiffness in a small, heterogeneous group of PH patients in a research context. Similar measurements in a larger cohort are required to investigate differences between PWV and RAC for estimation of MPA stiffness.